2020
DOI: 10.3390/cancers12061635
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs in Small Extracellular Vesicles Secreted by a Human Melanoma Xenograft in Mouse Brains

Abstract: The identification of liquid biomarkers remains a major challenge to improve the diagnosis of melanoma patients with brain metastases. Circulating miRNAs packaged into tumor-secreted small extracellular vesicles (sEVs) contribute to tumor progression. To investigate the release of tumor-secreted miRNAs by brain metastasis, we developed a xenograft model where human metastatic melanoma cells were injected intracranially in nude mice. The comprehensive profiles of both free miRNAs and those packaged in sEVs secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…The cells were administered at a depth of 3 mm. The number of cells used for the inoculation was determined in accordance with previous literature with the established human melanoma cell line M14 62 . For the procedure, the animals received anesthesia (9mg Ketamine-Hydrochloride (CP-Pharma Handelsgesell- schaft mbH, Burgdorf, Germany) + 1mg Xylazine (CP-Pharma Handelsgesellschaft mbH, Burgdorf, Germany) per 100g) intraperitoneally as well as subcutaneous prophylaxis against infection (10’000 I.E, benzylpenicillin potassium, InfectoPharm Arzneimittel und Consilium GmbH, Heppenheim, Germany) and analgesia (100 mg/kg Paracetamol (B. Braun Deutschland GmbH & Co. KG, Melsungen, Germany), Lidocaine (Aspen Germany GmbH, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were administered at a depth of 3 mm. The number of cells used for the inoculation was determined in accordance with previous literature with the established human melanoma cell line M14 62 . For the procedure, the animals received anesthesia (9mg Ketamine-Hydrochloride (CP-Pharma Handelsgesell- schaft mbH, Burgdorf, Germany) + 1mg Xylazine (CP-Pharma Handelsgesellschaft mbH, Burgdorf, Germany) per 100g) intraperitoneally as well as subcutaneous prophylaxis against infection (10’000 I.E, benzylpenicillin potassium, InfectoPharm Arzneimittel und Consilium GmbH, Heppenheim, Germany) and analgesia (100 mg/kg Paracetamol (B. Braun Deutschland GmbH & Co. KG, Melsungen, Germany), Lidocaine (Aspen Germany GmbH, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the results demonstrated the presence of tumor suppressor miRNAs in the total plasma, while exosome-derived miRNAs exhibited oncogenic functions. These findings suggest that cancer cells secrete tumor suppressor miRNAs into plasma and package oncogenic miRNAs in exosomes, promoting the interaction between cancer cells and their microenvironment to increase cancer cell survival and prepare a pre-metastatic niche [ 84 ].…”
Section: Functional Roles Of Different Components Of Exosomes In Cancermentioning
confidence: 99%
“…Later, Singh et al used patient-derived stem cell lines from lung-to-brain metastases to investigate the modulatory effect of STAT3 in brain metastasis initiating cells and found STAT3 and miR-21 functioned as cooperative orchestrators of stemness and tumor initiation in lung-derived brain metastases [ 43 ]. Loredana et al demonstrated that miR-21, secreted by melanoma cells in small extracellular vesicles contributed to brain metastasis of melanoma patients [ 44 ]. These suggested that tumor cells expressing miR-21 had a disposition to migrate towards brain tissue.…”
Section: Mirna Alterations Associated With Pnimentioning
confidence: 99%